Elexacaftor–Tezacaftor–Ivacaftor improves exercise capacity in adolescents with cystic fibrosis. Issue 11 (22nd July 2022) - Causer, Adam J.; Shute, Janis K.; Cummings, Michael H.; Shepherd, Anthony I.; Wallbanks, Samuel R.; Pulsford, Richard M.; Bright, Victoria; Connett, Gary; Saynor, Zoe L.
Abstract: Objective: Elexacaftor/Tezacaftor/Ivacaftor is a cystic fibrosis transmembrane conductance regulator (CFTR) modulator with the potential to improve exercise capacity. This case series of three adolescents with CF aimed to investigate whether 6 weeks treatment with Elexacaftor/Tezacaftor/Ivacaftor could improve exercise capacity in CFTR modulator naive adolescents with CF. Methods: Three adolescents (14.0 ± 1.4 years) with CF (FEV1 % predicted: 62.5 ± 17.1; F508del/F508del genotype) completed an exhaustive maximal cardiopulmonary exercise test on a cycle ergometer to determine peak oxygen uptake ( V ̇ V O2peak ) and measure changes in gas exchange and ventilation during exercise at 6 weeks. We also analyzed wrist‐worn device‐based physical activity (PA) data in two of the three cases. Validated acceleration thresholds were used to quantify time spent in each PA intensity category. Results: Clinically meaningful improvements in V ̇ V O2peak were observed in all three cases (+17.6%, +52.4%, and +32.9%, respectively), with improvements greatest in those with more severe lung disease and lower fitness at baseline. Although lung function increased in all cases, inconsistent changes in markers of ventilatory and peripheral muscle efficiency likely suggest different mechanisms of improvement in this case group of adolescents with CF. Device‐based analysis of PA was variable, with one case increasing and one case decreasing. Conclusion: In this case series, we have observed, for the first time, improvements in exercise capacity following 6 weeks of treatment with Elexacaftor/Tezacaftor/Ivacaftor. Improvements were greatest in the presence of more severe CF lung disease and lower aerobic fitness at baseline. The mechanism(s) responsible for these changes warrant further investigation in larger trials.